PENGARUH PENGALAMAN ON THE JOB TRAINING (OJT), KEMAMPUAN MEMASUKI DUNIA KERJA, INFORMASI MEMASUKI DUNIA KERJA TERHADAP KESIAPAN DUNIA KERJA (STUDI KASUS SISWA KELAS XII SMK MUHAMMADIYAH ULUJAMI PEMALANG JURUSAN OTOMOTIF TKR ): Dibuat Oleh Imam rosyadi, Fenilinas Adi Artanto, M. Yusuf Febrianto, S.Kom., M.Kom - Imam Rosyadi; fenilinas adi; muh yusuf (FEB Universitas Muhammadiyah Pekajangan Pekalongan, 2022)
This study aims to examine the effect of On The Job Training (OJT) experience, motivation to enter the workforce and work world information on workforce readiness. The research was conducted at the Nusa Mandiri Vocational School, Automotive Department (TBSM) Pemalang. population taken was all students of class X11 of Muhammadiyah Vocational School of Automotive (TKR) Pemalang, totaling 120 students using the saturated sample method. Data collection was done by interview and questionnaire. The analysis technique used in this study is multiple linear regression using SPSS (Statistical Product and Service Solutions) version 20 program used to analyze data. Based on the results of this study indicate that, (1) the experience of On The Job Training (OJT) significantly influences the readiness of the workforce. (2) motivation to enter the workforce does not have a significant effect on workforce readiness. (3) ability about the world of work has a significant effect on the readiness of the world of work. (4) On the Job Training (OJT) experience, motivation to enter the workforce and simultaneous workforce information have a significant effect on workforce readiness.